Proceso atención de enfermería en adulto mayor con cáncer uterino. - Mora Márquez, Mirna Milena (2023)
Cancer is a major health problem, given the high morbidity and mortality it causes. It is one of the most complex processes in nature and is the most complicated in the field of medicine. Cervical cancer is a multifactorial disease, which generally develops in the transformation zone of the squamo-columnar junction of the cervix, from precursor lesions after infection by the human papillomavirus, in the presence of other cofactors: genetic, environmental.5. The incidence of squamous cell carcinoma has decreased due to the introduction of cervical smear screening programs using the Papanicolaou technique in countries with effective and well-structured programs. This type of malignant tumor is much more frequent than small cell or cervical adenocarcinoma worldwide. Cervical cancer is one of the entities with the greatest impact and repercussions on women's health, particularly important in older adult women. It has been considered an emerging disease for only a few years, which may explain why many professionals still do not have sufficient information and requires a process of continuous training in order to keep up with the epidemiological circumstances. The social, human and economic consequences of cervical cancer make it an important problem for public health and humanity.